The significant of history curriculum in the development of active citizen: a critical analysis of the ICSS History, Malaysia - Salleh, Mohamad Johdi; Mohamad, Baharom; Ambotang, Abdul Said (2011)
This study discusses the aim and objectives of teaching and learning of history, Integrated Curriculum for Secondary School (ICSS), Malaysia. The introduction of this subject should help to develop skills in pupils in communication, understanding concepts, to extend vocabulary and use of language in different contexts, to encourage discussion, and, problem-solving. The important thing is that the pupil’s acquisition of historical skills and to the development of personality and selfconfident should each be systematically assessed in order to identify both progress and any need for further remedial or enrichment work. This is important in the production of motivated and active citizen who can learn effectively and be competent in their future jobs career. Consequently, the pupils are expected to appreciate and practise in daily life Malaysian multi-culture, appreciate the efforts and contributions of the national figures who had liberated and developed the nation, and, have historical and consciousness with regard to the existing community in the country. It is clear that history curriculum is the only subject at school to directly foster and develop active citizen towards the realisation of the Vision 2020 and 1-Malaysia.